PEMBUATAN TEH KOMBUCHA DAUN GAMBIR DENGAN PENAMBAHAN BEBERAPA KONSENTRASI MADU - Abdan Syakur; Yusmarini; Emma Riftyan (Fakultas Pertanian Universitas Riau, 2025)
Kombucha tea is a fermented beverage characterized by a sour taste with a slight sweetness. The basic ingredients of kombucha tea can be made using gambir leaf tea because it has high antioxidants. Gambir leaf tea has a bitter and astringent taste, therefore efforts are needed to reduce this by fermenting it and adding honey as a source of sugar. This study aims to determine the appropriate concentration of honey in making kombucha tea from gambir leaves. The study was conducted experimentally using a completely randomized plan (CRD) with 4 treatments and 4 replications. The treatment in this study was the addition of honey concentration (7.5, 10, 12.5 and 15%). The parameters observed in this study were total acetic acid, acidity level (pH), total dissolved solids, antioxidant activity and sensory assessment. Data obtained from the observations were statistically analyzed using analysis of variance (ANOVA) on IBM SPSS software version 25 and continued with Duncan's multiple range test (DMRT) at the 5% level. The results showed that the addition of different honey concentrations had a significant effect on total acetic acid, pH, total dissolved solids, and antioxidant activity. Descriptive and hedonic sensory assessments but did not have a significant effect on aroma descriptively. Gambir leaf kombucha tea treatment (KM4) with a honey concentration of 15% had a total acetic acid value of 0.48%, acidity level 2.96, total dissolved solids of 14.85, and antioxidant activity of 84,45 ppm. Brown in color, fermented aroma and slightly sweet sour taste and was liked by the panelists overall.